Development of conditional-siRNA programmable riboswitch for targeting adverse cardiac remodeling - Priyanka Gokulnath; Ane M. Salvador; Caleb Graham; Si-ping Han; Guoping Li; Ramaswamy Kannappan; Christopher Azzam; Michail Spanos; Lisa Scherer; Palaniappan Sethu; John Rossi; William A. Goddard, III; et al. (Molecular Therapy: Nucleic Acids)
Heart failure (HF) remains a significant healthcare burden, with an unmet need for novel therapies to target the preceding pathological hypertrophy in HF patients. Here we report the development of novel conditional-siRNA (Cond-siRNA) constructs that are selectively activated by disease-specific RNA biomarkers to enable cell-specific inhibition of a target disease-causing RNA. We designed a Cond-siRNA that can be activated by Nppa mRNA, upregulated specifically in cardiomyocytes (CMs) under pathological stress, to silence the key pro-hypertrophic gene calcineurin (CaN) A-a by the effector small interfering RNA (siRNA). In both neonatal rat ventricular myocytes (NRVMs) and H9c2 CMs, Cond-siRNA showed minimal baseline activity but selectively silenced CaN upon Nppa mRNA induction by phenylephrine (PE) stress in cell culture models and pressure overload (PO) in a heart-on-a-chip model. In NRVMs, Cond-siRNA reduced CaN mRNA only after PE or PO, but not with vehicle, confirming Nppa-specific activation. This specificity was further validated as Cond-siRNA did not affect CaN in cardiac fibroblasts or T cells lacking Nppa. Reduced CaN protein levels and NFATc1 nuclear translocation correlated with decreased NRVM hypertrophy after PE treatment, confirming Cond-siRNA’s efficacy. This study offers proof-of-concept for Cond-siRNA as a targeted therapy to mitigate hypertrophic progression, paving the way for novel HF treatments.